2023
DOI: 10.1002/leap.1533
|View full text |Cite
|
Sign up to set email alerts
|

A technology‐based, financially sustainable, quality improvement intervention in a medical journal for bilingualism from submission to publication

Abstract: Key points While English is the dominant language in scientific literature, there are many reasons for introducing bilingualism in academic journals. Bilingualism has generally been avoided due to the perception of high costs and possible inconsistencies between the source language article and the translated version. A medical journal based in Santiago, Chile, carried out a two‐year‐long quality improvement intervention to overhaul the peer review, copyediting, translating and publication technologies to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The rise of AI technology will facilitate the translation of articles in natural and medical sciences from local languages into English because most subject‐specific terms are imported into non‐Anglophone countries from Anglophone countries, the centre of knowledge production, and require much less human intervention. The successful application of the bilingual publishing policy to Medwave has shown that AI‐based and human‐revised translation of medical articles from Spanish into English within a limited budget is feasible (Bachelet & Rousseau‐Portalis, 2023). The translation of academic articles in social science and arts journals from local languages into English, by contrast, may require more human interventions from translators because some expressions may have no equivalents in English due to their close connection with non‐Anglophone culture, ideology, history and society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rise of AI technology will facilitate the translation of articles in natural and medical sciences from local languages into English because most subject‐specific terms are imported into non‐Anglophone countries from Anglophone countries, the centre of knowledge production, and require much less human intervention. The successful application of the bilingual publishing policy to Medwave has shown that AI‐based and human‐revised translation of medical articles from Spanish into English within a limited budget is feasible (Bachelet & Rousseau‐Portalis, 2023). The translation of academic articles in social science and arts journals from local languages into English, by contrast, may require more human interventions from translators because some expressions may have no equivalents in English due to their close connection with non‐Anglophone culture, ideology, history and society.…”
Section: Discussionmentioning
confidence: 99%
“…To date, specific research on the adoption of these two language policies by non-Anglophone journals has been rare. One exception is the contribution of Bachelet and Rousseau-Portalis (2023), who reported how they as the editors of Medwave, a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation